Lycopene promotes a fast-to-slow fiber type transformation through Akt/FoxO1 signaling pathway and miR-22-3p. (May 2021) - Wen, Wanxue; Chen, Xiaoling; Huang, Zhiqing; Chen, Daiwen; He, Jun; Zheng, Ping; Yu, Jie; Luo, Yuheng; Yan, Hui; Yu, Bing
Graphical abstract: Highlights: Lycopene supplementation induces a fast-to-slow fiber type transformation. The Akt/FoxO1 signaling is activated by lycopene. Akt inhibitor wortmannin eliminates the promoting effect of lycopene on muscle fiber type transformation. miR-22-3p involves in lycopene-induced muscle fiber type conversion. Abstract: This study investigated molecular mechanisms of lycopene regulating muscle fiber type transformation in vitro and in vivo . Remarkably, TNNI1 protein level was increased, while TNNI2 protein level was decreased in C2C12 myotubes and in mice after lycopene treatment. Lycopene also enhanced enzyme activities of succinic dehydrogenase and malate dehydrogenase and reduced lactate dehydrogenase activity. Meanwhile, lycopene markedly upregulated the protein expressions of P-Akt and P-FoxO1 and decreased FoxO1 protein level. However, specific blocking Akt/FoxO1 signaling by wortmannin effectively eliminated lycopene-induced upregulation of slow MyHC and downregulation of fast MyHC in C2C12 myotubes. In addition, lycopene effectively inhibited miR-22-3p expression in C2C12 myotubes and in mice, whereas miR-22-3p mimics attenuated transformation from fast glycolytic fiber to slow oxidative fiber caused by lycopene. Our findings provided the first evidence that lycopene promoted muscle fiber type transformation from fast-twitch to slow-twitch through Akt/FoxO1 pathway and miR-22-3p.